Causes of industrial land-use regulations in China: A share tenancy perspective. (November 2022) - Gao, Fugang; Ma, Xianlei; van der Krabben, Erwin; Ploegmakers, Huub; Shi, Xiaoping
Abstract: Industrial land-use regulations (ILURs) are important policy instruments used by local governments in China to remedy the side effects of industrial production and to protect scarce land. In recent years, this type of policy has become increasingly stringent. To explain the reasons for using them, we propose an analytical framework in which ILURs are integrated into a land-leasing contract between the firm and the local government. This contract is theorized as a share tenancy with an exogenous rental percentage, and the stringency of ILURs is chosen to minimize transaction costs. In this setting, the region with a higher scarcity of industrial land or higher redevelopment costs of stock industrial land is supposed to impose a shorter leasing term and tighter control of firms' inputs and outputs (FIOs); meanwhile, firms with higher anticipated productivity will be offered a longer leasing term. These propositions are consistent with the patterns we reveal by analyzing the regulatory policies of three Chinese cities around 2015 and the detailed regulations and default clauses stipulated industrial land-leasing contracts in 2017 in Shanghai. Highlights: ILURs in China can be integrated into a land-leasing contract between the firm and the local government. Regulatory stringency that refers to FIOs types, contract length and the enforcement is used to minimize transaction costs. Regions with a higher scarcity of industrial land is supposed to impose a shorter leasing term and tighter control of FIOs. Firms with higher anticipated productivity will be offered a longer leasing term.